Efektivitas Ventilator dalam Proses End of Life dan Tinjauannya Menurut Pandangan Islam - Yulya Mauliddina; Ferryal Basbeth; Muhammad Arsyad (Lembaga Penelitian Universitas YARSI, 2020)
Background: A mechanical ventilator is a device used to help with respiratory function. Its use is indicated for patients with hypoxemia, severe hypercapnia and respiratory failure. Mechanical ventilator is one of the important and widely used aspects for critical patient care in the Intensive Care Unit (ICU). Methods: This research was conducted with non-probability sampling techniques. Non-probability sampling techniques was determined by purposive method, which is to determine the criteria first, then the samples are taken according to predetermined criteria. Results: As much as 98 medical records taken from the Juwita Bekasi Hospital ICU from 2013-2017 showed that 3 patients showed effective results for ventilator installation and 95 patients showed ineffective results. Conclusion: Based on medical record in Juwita Bekasi Hospital from 2013 to 2017, The mechanical ventilation installation was not effective and only has 1% effectivity.